First detection of Trypanosoma vivax in cattle in the state of Bahia, Brazil, based on parasitological and molecular analyses - Silva Ferreira Gomes, Hayala Caroline [UNESP]; de Jesus Genipapeiro, Igor Leonardo; Andrade, Fabíola Teixeira; de Campos Vieira Barbosa, Danielle; Pacheco, Leonardo Ribas; Silva, Regiane Pereira Benevides; Patrocínio, Epaminondas; de Jesus Barbosa, Cristiane; Ribas, Jorge Raimundo Lins; Barbosa, Luciana Veiga (Universidade Estadual de Londrina, 2021)
We report the first detection of Trypanosoma vivax in Bahia state based on blood smear and PCR analyses. A total of 623 bovine blood samples were collected over two years. Parasitological analysis by smear technique detected the presence of T. vivax in 0.3%, while molecular analysis by PCR showed a prevalence in 18.9% of the samples. This study demonstrated the higher sensitivity of molecular analysis in the diagnosis of hemoparasitosis caused by T. vivax in dairy cattle herds.
Primeira detecção de Trypanosoma vivax em bovinos no estado da Bahia, Brasil baseada em análises parasitológica e molecular
Keywords: Blood smears; Northeast of Brazil; PCR; Trypanosomiasis